Identification of Informatics Engineering Student Learning Styles in the Independent Learning Era - Sumarsono Sumarsono; Annisa Firanti (Universitas Pendidikan Ganesha, 2021)
This study aims to analyze the characteristics of student learning styles based on visual, auditory and kinesthetic learning styles as well as the characteristics of learning styles based on the surrounding environment. The research method uses descriptive qualitative. The research sample was using a random technique so that the total sample was 43 students. The instrument of this research is a questionnaire with 3 indicators of visual, auditory and kinesthetic as well as how the role of the surrounding environment in determining student learning styles. Supporting instruments using interview techniques. The data analysis technique used descriptive statistics and qualitative descriptive analysis. Based on the results of the study, it is known that the identification of student characteristics on learning styles is seen from visual learning styles (28%), auditory (31%) and kinesthetic (41%). Characteristics of learning styles in the form of environmental identification based on student interaction are learning alone (23%), studying with others in a calm state (28%) and learning with others by doing something (49%). Identification of the environment based on outdoor learning places is 77% and the percentage of indoor learning is (23%). Based on the identification results, the majority have the habit and desire to learn outside the classroom in developing their competencies, this is in line with the heutagogy learning strategy, namely independent learning, developing their own learning strategies, developing theoretical and practical materials together with people or groups who can work together.